PENGEMBANGAN E-MODUL BERBASIS PENDIDIKAN MATEMATIKA REALISTIK PADA MATERI BILANGAN BULAT KELAS VII SMP - Eka Fardanilla (Departemen Matematika, 2020)
This research aims to develop an e-module based on realistic mathematics education in integer material of class VII SMP which is valid and practical. This type of research is a design research type of development studies with the Plomp development model which consists of three stages, namely preliminary research, development or prototyping phase, and assessment phase. The research is in SMPN 3 Batusangkar to students of class VII.2 and VII.3. The date is the qualitative and quantitative data. The data collection instruments were validity instruments and practicality instruments. The data obtained were then analyzed using quantitative and qualitative analysis techniques. Based on the validation results, the e-module is considered valid with a validity level of 89.44%. The results of the students' responses describe this e-module that is practical to be applied in learning. This was shown in the one-to-one evaluation stage the practicality level was 92.42% and at the small group evaluation stage, the practicality level was 94.24%.Keywords: e-module, Realistic Mathematics Education, valid, practical